Etnobotani Bahan Makanan Tradisional di Desa Bonjeruk Kecamatan Jonggat Kabupaten Lombok Tengah - Rosalina Edy Swandayani; Arista Suci Andini; Meilinda Pahriana Sulastri (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Ethnobotany studies direct relationship between humans and plants that are used traditionally, one of which examines the use of plants as ingredients in culinary. West Nusa Tenggara Province (NTB) is a province in Indonesia with a distinctive culture including a variety of cuisines, one of which is in Bonjeruk Village, Jonggat District, Central Lombok. The culinary culture of the Sasak people use of plants as their main ingredients. In addition, this traditional food is the potential for promotion to support tourism. The purpose of this study was to inventory and identify the types of plants used for traditional food ingredients as a basis for developing local culinary-based tourism in Bonjeruk Tourism Village. This research is also expected to be able to document and preserve knowledge related to traditional food before this knowledge becomes extinct. The research was conducted in October-December 2022. The selection of subjects was carried out using the snowball sampling method and interviews were conducted using an in-depth interview technique. Identification of plants is done by way of inventory through direct observation. Based on the research results, it was found that 40 species were used in 23 families. The types of plants are utilized in 22 traditional food menus.